The Increase In Raw Material Prices And It’s Impact On The Income Of Tempe Producers In Kepahiang District - Since Sovia Elita; Yossie Yumiati; Evi Andriani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Continuous increase in soybean prices results in reduced ability of tempe producers to continue to produce. If the price increase continues, it is feared that many tempe producers will not be able to continue their business because their income cannot be used to cover the increase in production costs. This study aims to influence the increase in soybean prices (Glycine max (L.) Meril) on the income of small businesses. The research method used is quantitative methods and simple linear regression analysis. The results of the study show an increase in soybean prices from 2019 to 2021. Increases in soybean prices start from Rp. 1,000 to Rp. 2,000 annually. The effect of increasing soybean prices (Glycine max (L.) Meril) on the income of small tempe businesses in Kepahiang District, Kepahiang Regency can be seen with a significant value of 0.019 because the significant value is less than 0.05, it can be concluded that there is a significant influence from the increase in soybean prices (Glycine max (L.) Meril) on the income of small tempeh businesses in Kepahiang District, Kepahiang Regency